The Effectiveness Of Utilizing Productive Zakat By Baznas In Empowering Msmes - Renny Agustina; Rafika Edyan Putri; Amiroh Rona Zakiyah (International Journal of Business and Quality Research, 2026)
Abstract This study aims to analyze the effectiveness of productive zakat utilization in empowering Micro, Small, and Medium Enterprises (MSMEs) entitled to beneficiaries in Indonesia. The study employed a qualitative approach based on documentation studies, utilizing secondary data from zakat institution reports, scientific publications, and previous research. The data were analyzed using content analysis techniques to identify implementation patterns, impacts, and factors influencing program effectiveness. The results indicate that productive zakat contributes to increasing income, developing businesses, and encouraging the economic independence of mustahik. Programs implemented by the National Zakat Agency (BAZNAS) and other zakat institutions provide not only capital assistance but also training and mentoring. However, program effectiveness varies, with programs with intensive mentoring and good governance tending to have more sustainable impacts. This study emphasizes the importance of strengthening the empowerment process, particularly in terms of mentoring and governance, so that productive zakat can function optimally in supporting poverty alleviation and strengthening MSMEs. Keywords: productive zakat; MSMEs; economic empowerment; program effectiveness; mustahik